Pengaruh Bioconc Expired Dalam Kuat Tekan Beton - Arifien Nursandah; Faizah Rizki Jannah (Universitas Muhammadiyah Surabaya, 2017)
The method used in this research is the method of the Department of Environment (DOE) which is usually referred to the design of the English manner stipulated in SNI 03-2834-2000 namely